1999
DOI: 10.1002/(sici)1520-7560(199909/10)15:5<362::aid-dmrr58>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

The Greek contribution to diabetes research

Abstract: Interest in diabetes mellitus research has escalated in Greece during the last decade. This may be attributed to the realization that diabetes is becoming a major problem for the Greek population, the effect of the St Vincent Declaration in passing specific government legislation, and the founding of the National Hellenic Center for the Prevention and Treatment of Diabetes and its Complications. Research areas include epidemiology, etiopathogenesis, glucose metabolism, complications, prevention and treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 170 publications
(158 reference statements)
0
2
0
2
Order By: Relevance
“…A previous report on the epidemiology of childhood-onset Type 1 diabetes in Crete published data from the 12-year period 1990-2001. During that period the standardized annual incidence rate reported was 6.1 per 100 000 person-years-atrisk [11], which was lower than that reported by Bartsocas [5] in a 7-year survey in the greater Athens area, conducted around the same period [5].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…A previous report on the epidemiology of childhood-onset Type 1 diabetes in Crete published data from the 12-year period 1990-2001. During that period the standardized annual incidence rate reported was 6.1 per 100 000 person-years-atrisk [11], which was lower than that reported by Bartsocas [5] in a 7-year survey in the greater Athens area, conducted around the same period [5].…”
Section: Introductionmentioning
confidence: 54%
“…Greece is listed among the countries with high rates, with 10.4 new cases per 100 000 per year according to the International Diabetes Federation (IDF) estimates for 2013 [4]. Α 7-year study, conducted from 1989 to 1995 in the greater Athens area, reported an average incidence rate of 9.7 per 100 000 person-years-at-risk [5].…”
Section: Introductionmentioning
confidence: 99%
“…Υπάρχουν ισχυρές επιδημιολογικές, ορολογικές και μοριακές αποδείξεις που συσχετίζουν τη λοίμωξη με ιό Coxsackie B4 με την ανάπτυξη διαβήτη τύπου Ι στον άνθρωπο [868]. Είναι αξιοσημείωτο ότι η συχνότητα εμφάνισης περιστατικών διαβήτη τύπου Ι στην Αθήνα (<10 στα 100.000 παιδιά) είναι υψηλότερη σε σχέση με τη συχνότητα που παρατηρείται σε πέντε πόλεις της Βορείου Ελλάδας (<5 στα 100.000 παιδιά) [869,870]. Επιπρόσθετα, η συχνότητα περιστατικών διαβήτη τύπου Ι στις αστικές περιοχές (10/100.000) είναι σχεδόν διπλάσια της συχνότητας που υπολογίζεται στις αγροτικές περιοχές (4,21/100.000) [871].…”
Section: συζητησηunclassified
“…Ραρά το γεγονόσ ότι θ Ελλάδα εμφανίηει πολφ χαμθλά ποςοςτά διαβιτθ τφπου 1 (Dacou-Voutetakis, Karavanaki et al 1995, Bartsocas 1999, Lionis, Bathianaki et al 2001, δεν ιςχφει το ίδιο για το ςακχαρϊδθ διαβιτθ τφπου 2, που αυξάνεται με ταχφ ρυκμό τόςο ςε αςτικζσ όςο και ςε αγροτικζσ περιοχζσ. (Panagiotakos, Pitsavos et al 2005).…”
Section: επιδθμιολογία του ακχαρϊδθ διαβιτθ ςτθν ελλάδαunclassified